LANGUAGE, SUBJECT AND (DIS)IDENTIFICATIONS IN (DIS)COURSE:: THE TEACHING AND LEARNING OF ENGLISH LANGUAGE-CULTURE IN THE MODULAR TEACHING ORGANIZATION SYSTEM (SOME) - Rodrigues Lopes , Lucas; Luís Silveira, Éderson; Ranieri Furtado, Geciel (Revista de Letras, 2024)
This research seeks to investigate the words of riverside students about the teaching-learning of English Language-Culture, considering the (dis)identifications of such subjects, thinking of them as constituents of/in their subjectivities and ways of life among forests and rivers located in the surroundings of the city of Cametá-PA, in order to track the emerging meaning effects. Therefore, this investigation focuses on the representations of riverside students in the context of High School (SOME), with regard to English Language-Culture. The theoretical-methodological path was through Discourse Studies considering the contributions of Foucault (1996), Coracini (2007, 2016), Orlandi (1999) and Lopes (2018, 2020); regarding the concept of identity, we started from the theoretical assumptions of Bauman (2013) and Hall (2005). In the meantime, aiming to analyze the data, an interview was carried out with riverside students from the town of Mutuacá de Baixo, Cametá/PA, who study in the SOME Modality. In the analyzes carried out, riverside subjects reveal that their (dis)identifications influence the English Language-Culture teaching-learning process for riverside people, with such instances being responsible for creating resistance in students in relation to their learning.